A obra de Ângelo Agostini e a litografia como arte na luta pela abolição da escravatura - Barata, Mário (Ciência & Trópico, 2011)
RESUMOA história da criação estética mostra o lugar do desenhista e caricaturista Ângelo Agostini, fundador da Revista Ilustrada, e de suas litografias, como também o reconhecimento dos líderes do movimento antiescravista. Nessas litografias, vê-se a importância da arte de Agostini tanto de seu valor tonal e efeitos estéticos, quanto de seu empenho narrativo e crítico e arte política através de “charges” feitas com naturalismo mostrando cenas ocorridas.ABSTRACTÂngelo Agostini’s work and litography as art in the struggle for the Abolition of slavery. v. 16, n. 1, p. 19-27, jan./jun. 1988.The History of esthetics creation shows the place of Ângelo Agostini. The designer and caricaturist, was the founder of Revista Ilustrada, and its litographies, but also the recognizement of the leaders of the anti-slavery movement. It is seen in these litographies the importance of Agostini’s art as much as its tonal value and esthetical effects as by its narrative and critical performance and political art through “charges” done with naturalism about facts of the past time.RÉSUMÉL’oeuvre d’Ângelo Agostine et la lithographie comme art dans la lutte pour l‘abolition de l’esclavage. v. 16, n. 1, p.19-27, jan./jun. 1988.L’histoire de la création esthétique montre la place du dessinateur et caricaturiste Angelo Agostini, fondateur de la Revista Ilustrada et de ses lithographies, et aussi la reconnaissance des chefs du mouvement anti-esclavagiste. On constate dans ses lithographies l’importance de l‘art d’Agostini, soit dans sa valeur tonale et ses effets esthétiques, soit dans la force narrative et critique et l‘art politique à travers les “charges” d'un naturalisme fait de scènes réelles.